The Influence of ERP-SAP Implementation and Inventory Management on Production Efficiency through Inventory Control Performance Using Partial Least Square (PLS) Method - Pradata, Amelia Putri; Ernawati, Dira (The Indonesian Journal of Computer Science, 2024)
PT XYZ is the largest manufacturing company in Indonesia that produces biscuits with the support of the SAP system, which has integrated data from each division, especially the inventory control division. Due to the accessibility of real-time data, it was observed that there were two late arrivals of raw materials, causing the company to only achieve 75% of the weekly production target. Therefore, this study aims to determine the effect of ERP-SAP implementation and inventory management on smooth production and provide recommendations for improvement through inventory control performance at PT XYZ. The method used is Partial Least Square (PLS) which uses SmartPLS. Based on the research conducted, it was found that the implementation of ERP-SAP does not have a positive impact on production flexibility, but has a positive impact on inventory management performance, and then inventory management directly positively affects production efficiency and inventory control performance